WHEN ATHLETIC VICTORY AND FATHERHOOD DID MIX: THE COMMEMORATION OF DIAGORAS OF RHODES. (11th June 2018) - NICHOLSON, NIGEL
Abstract: The fame of the great boxer Diagoras of Rhodes was intimately, and uniquely, bound up with the fame of his children: for no other classical or archaic victor were his children so central to his own commemoration. This paper will explore that centrality, showing the extent to which Diagoras' portrayal across all media — not only in epinician and sculptural dedications, but also in the oral tradition — was unique in emphasizing his status as a father, and seek to explain the choice. I will argue that the portrayal of Diagoras as a father, subject to the normal biological rhythms of life, signified a particular type of politics that favored networking and connections between cities, promoting, in particular, the synoecism of Rhodes' three cities.